Strategi Abduktif-Deduktif Pada Pembelajaran Matematika Dalam Peningkatan Disposisi Siswa - Shodikin, Ali (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2015)
Learning with abductive-deductive strategy is the type of a new approach learning of mathematical thought processes. The purpose of this research is to improve students’ mathematical disposition using abductive-deductivestrategy. Research carried out a nonrandomized control group, prescalepostscale design in eleventh class in one high school in Pati regency, Central Java. Data analysis was conducted quantitative-qualitative research by category early mathematical ability (KAM) and overall. In addition, purpose of research is to also analyze the interaction between learning and KAM. The results showed that the increase of students who got a mathematical disposition learning with abductive-deductive strategy have same result with the students who got expository. In more detail, the category of upper class and middle class is showing the same increase. While the below categories has an increased disposition smaller than the expository. Interaction between learning and KAM to increase the disposition showed no signifiant relationship. This research expected teachers to notice early mathematical ability of students in mathematicsand give special attention related to increase in students’ mathematical disposition, due to certain student groups despite a suitable learning to improve students’ mathematical ability and disposition, however differentthe early mathematical ability showed different resultsKeywords: Strategi Abduktif-Deduktif, Peningkatan, Disposisi Matematis.